TRANSFORMATION OF BRANCH OFFICE BUSINESS MODEL (Housing & Development Board of Singapore) - Tey, Eng Soon Thomas (2010)
EXECUTIVE SUMMARY Housing & Development Board (HDB) serves a wide variety of customers that ranges from those who are highly educated to those who are illiterate. This wide customer base results in customers requiring different channels to contact HDB. To make it convenient for the customers, Branch Offices (BO) were set up in the HDB heartlands to serve each town. Its close proximity to the ground also made it an ideal channel to promote the building of communities through close workings with the residents and grassroots organizations. With the tightening of government funding, the challenge is for HDB to continue providing the same or better level of customer service in the most cost effective manner without any increase in resources. To meet this challenge, a cost–effective business model was developed with the ultimate goal is an integrated solution that spanned physical boundaries. The Service Centre concept emerged as a more cost efficient business model, with the implementation of a file-less operation model being key. There is also a need to review the existing services provided at the Branch Offices, particularly with the intention to hive off non-core functions to focus on being a housing authority and to improve the efficiency and effectiveness of the core functions that continue to remain key to the Branch Offices’ operations. This report covers the review and development of the BO service model and the implementation of the file-less operation model. Two other case studies are also reviewed under the scope of the Transformation of Branch Office Business Model. One pertains to the outsourcing of non-core function (the outsourcing of the car parking enforcement function by replacing the existing long term parking system using the RFID technology) and the other involves the re-engineering of a core business function (revamping telephone enquiry function with the implementation of VoIP and Virtual Call Center).